A qualitative study exploring community pharmacists' awareness, attitudes and perceptions about drive-thru community pharmacy service in Malaysia during COVID-19 - Bayan F. Ababneh; Siew Chin Ong; Iffat Elbarazi; Hisham Z. Aljamal; Rabia Hussain (Taylor & Francis Group, 2024)
ABSTRACTIntroduction: Drive-thru services are not given sufficient focus in the community pharmacy setting which was highlighted during COVID-19, particularly in Malaysia. This study aimed to explore the community pharmacists' perspectives regarding drive-thru community pharmacy service during COVID-19 in Malaysia.Methods: In-depth online semi-structured individual interviews were conducted among 25 community pharmacists working in Malaysia. All interviews were conducted between March 2022 and May 2022 and were audio-recorded and transcribed verbatim, and then analysed by thematic analysis.Results: Thematic analysis yielded seven major themes, 1-familiarity with drive-thru community pharmacy service during COVID-19, 2-willingness toward this service during COVID-19, 3-perceived benefits toward drive-thru community pharmacy service during COVID-19, 4-perceived disadvantages toward this service, 5-barriers toward drive-thru community pharmacy service, 6-factors affecting the preference toward this service, and 7-facilitators to drive-thru community pharmacy service. Enhancing social distancing and preventing the spread of COVID-19 were the major perceived benefits of this service during COVID-19 as reported by participants.Conclusion: Overall, community pharmacists reported positive attitudes toward drive-thru community pharmacy service during COVID-19. However, concerns about poor communication between the pharmacist and the patient, limited counselling, and dispensing errors were acknowledged. These concerns would need to be addressed to improve the provision of drive-thru community pharmacy service.